Lack of understanding in fibromyalgia and rheumatoid arthritis: the Illness Invalidation Inventory (3*I). Issue 11 (24th May 2010) - Kool, M B; van Middendorp, H; Lumley, M A; Schenk, Y; Jacobs, J W G; Bijlsma, J W J; Geenen, R
Abstract : Background: Patients with rheumatic diseases may face 'discounting' (denying and patronising) or 'lack of understanding' because of having symptoms without external clinical signs, but instruments to assess such invalidation experiences are lacking. Objectives: To develop and evaluate the Illness Invalidation Inventory (3*I), to compare invalidation experiences of two groups of patients who differ in visual signs and laboratory findings—rheumatoid arthritis (RA) and fibromyalgia—and to examine the association of invalidation with health status. Methods: A questionnaire (eight items with respect to five sources: spouse, family, medical professionals, work environment and social services) was constructed. It was completed by 142 patients with RA and 167 patients with fibromyalgia. Results: Principal axis factoring with oblimin rotation yielded two factors with high internal consistency (α>0.70): 'discounting' (five items) and 'lack of understanding' (three items). Patients with fibromyalgia experienced significantly more discounting and lack of understanding from their family, medical professionals, colleagues and social services than did patients with RA. Both patient groups experienced more invalidation from social services, colleagues and family than from medical professionals and spouses. More discounting and lack of understanding correlated with poorer mental well-being and social functioning in both patient groups. Discounting correlated with more physical disability and pain in patients with RA. Conclusions: The 3*I is a brief, reliable instrument for assessing patients' perceptions of invalidation from different sources, which differ between patient groups and are associated with health status. Future validation research should clarify the clinical impact of invalidation on treatment adherence and outcome.